2004
DOI: 10.1110/ps.03581904
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a hybrid random ping‐pong mechanism of catalysis for NodST: A mass spectrometry approach

Abstract: An efficient enzyme kinetics assay using electrospray ionization mass spectrometry (ESI-MS) was initially applied to the catalytic mechanism investigation of a carbohydrate sulfotransferase, NodST. Herein, the recombinant NodST was overexpressed with a His 6 -tag and purified via Ni-NTA metal-affinity chromatography. In this bisubstrate enzymatic system, an internal standard similar in structure and ionization efficiency to the product was chosen in the ESI-MS assay, and a single point normalization factor was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
39
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…In so doing, we have successfully identified a sulfated enzyme intermediate, which was predicted by our previous study of NodST catalytic mechanism using an ESI-MS kinetic assay [23]. It is also shown that information regarding solution binding affinities can be obtained in the gas phase using ESI-FTICR mass spectrometry.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In so doing, we have successfully identified a sulfated enzyme intermediate, which was predicted by our previous study of NodST catalytic mechanism using an ESI-MS kinetic assay [23]. It is also shown that information regarding solution binding affinities can be obtained in the gas phase using ESI-FTICR mass spectrometry.…”
mentioning
confidence: 69%
“…In a similar manner, NodST can utilize chitobiose as the acceptor substrate to produce sulfated chitobiose (Scheme 1). Previous studies have shown that the substrate, PAPS, and the product inhibitor, 3Ј-phosphoadenosine 5Ј-phosphate (PAP), bind to NodST with the binding constants of 6.7 M and 1.8 M, respectively [22,23]. Additionally, mass spectrometry was used to show that NodST catalyzes the sulfation using a random hybrid ping-pong Bi-Bi mechanism, supporting the formation of a sulfated-NodST intermediate [23].…”
mentioning
confidence: 97%
“…Esaki et al reported a novel catalytic mechanism for L-2-Haloacid dehalogenase involving a cyanoalanine intermediate revealed by LC/MS monitoring of the enzymatic reaction [16]. Likewise, Leary and coworkers reported the identification of a sulfated NodH sulfotransferase (NodST) intermediate formed in a hybrid Ping-Pong mechanism using Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry [17]. A facile and broadly applicable ESI-MS assay developed by Leary and coworkers has been used for kinetic analyses on several enzyme systems such as glutathione S-transferase (GST) [27], hexokinase [28], and NodH sulfotransferase (NodST) [29].…”
mentioning
confidence: 99%
“…The mass spectrometry assay is especially useful because traditional spectrophotometric assays are not applicable to NodST kinetics since no shift in absorption accompanies sulfuryl group transfer. Using this assay, precise and accurate kinetic data were generated for all the enzymes above, and for the first time, a hybrid Ping-Pong Bi-Bi mechanism was unraveled for NodST [17]. A distinct feature of the ESI-MS assay is that product quantification is realized by monitoring the product ion in relation to an internal standard ion in a quenched reaction solution, allowing different product ions of different mass to charge ratio to be monitored and quantified simultaneously in one reaction system.…”
mentioning
confidence: 99%
“…Recently, the development of soft ionization techniques, such as electrospray ionization (ESI), has made MS an excellent complementary technique to conventional methods for studying enzyme kinetics (24)(25)(26)(27)(28)(29)(30). A facile and broadly applicable ESI͞MS assay developed by Leary and coworkers has been implemented for kinetic analyses and substrate specificity evaluation of several enzyme systems such as glutathione S-transferase (26), hexokinase (27), phosphoglucomutase (28), and NodH sulfotransferase (29,30). Herein, a somewhat different ESI͞MS technique was used to develop assays for NovL and NovM individually and in tandem.…”
mentioning
confidence: 99%